A pena Montelliana: a criação da Saga Maranhense no diário do escritor - VIEIRA, Mauro Cezar Borges (2022)
The process of literary creation is an object of study that has been gaining adherents in Brazil since 1990s, since the appearance of the first researches that used the assumptions of genetic criticism that appeared in France in the late 1960s and early 1970s With the arrival in Brazil and the constant change of assumptions, the idea of process documents became a primordial part of genetic studies. Thus, autobiographical texts began to be an integral part of this type of research. Following this assumption, this research aims to analyze the process of literary creation of the Saga Maranhense by Josué Montello through his diaries. In this scope, we will seek to demonstrate the characteristics of the diary genre and the way in which Josué Montello's diaries relate to this tradition, describe the research field of genetic criticism, passing through its history and current assumptions, and then we will study diaries of the author with a view to understanding the process of creating his Saga Maranhense. For this, we used the works of Lejeune (2009; 2014) with regard to autobiographical literature and, more specifically, the diary genre, Pino and Zular (2007) and Salles (2010; 2011; 2016; 2017) , with regard to the methodological procedures of genetic criticism and the categories that will be analyzed, which include the author's poetic project, chance, raw material, dialogues with the work in process, with the literary tradition, with the receiver, the tensions between limit and possibility, form and content, finishing and incompleteness, among others. We will also use several authors such as Cândido (2006), Souza (2010), Oliveira (2017) among others, in an attempt to better explain the concepts that will be raised. The methodology, therefore, will be the bibliographical review, both theoretical and collected in Josué Montello's diaries, in a qualitative approach. We seek, therefore, to fill a gap with regard to research on Josué Montello's diaries, from the Saga Maranhense, taken in its unit and, mainly, from this author's literary creation process.